frieze - The business of contemporary art: the evolution of the UK's leading contemporary arts magazine and fair - Hussels, Stephanie; Brown, Robert; Titterington, Kathryn (Senate Hall, 2010)
The case study deals with the creation and growth of Frieze in London to become a global leader in the contemporary art industry. Developed by two young college graduates, Matthew Slotover (a psychology graduate) and Amanda Sharp (a Politics Philosophy and Economics graduate), assisted by Tom Gidley (an art college student), the first edition of the Frieze magazine appeared in June 1991. By focusing on art galleries as key customers and by applying their expertise in desktop publishing, Frieze has grown into a significant company with 44 employees and a turnover exceeding £ 5 million. Today, Frieze is the top contemporary art magazine in Europe, also gaining a strong position in the US. Frieze Art Fair in London, launched in 2003, has become one of the top-tier art fairs globally. The case provides a detailed account of how the business strategy evolved and the process use to find profit opportunities. The case enables analysis of the circumstances and growth of the business to date and offers the challenge to use the insights gained from the analysis to determine an appropriate growth strategy from the many options now open for the business in 2008. A detailed Teaching Note is available with analysis and suggestions for questions to help stimulate discussions in the classroom. Keywords: arts industry, business growth strategy, entrepreneurship, innovation, new venture creation.
Keywords: arts industry|business growth strategy|entrepreneurship|innovation|new venture creation